PENERAPAN MODEL RECIPROCAL TEACHING DENGAN GAME SMART CASE UNTUK MENINGKATKAN MINAT BELAJAR BIOLOGI DI SMA NEGERI 1 ANGKOLA TIMUR - Elwidani Siregar; Iskandar Safri Hasibuan; Yusni Atifah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2017)
The problem in this research is the low interest of student biology in class X3 SMA Negeri 1 Angkola Timur. To overcome this problem, this research applied the learning model of Reciprocal Teaching with Game Smart Case on the subject of the ecosystem in class X3 SMA Negeri 1 Angkola Timur can increase student biology interest. The research method used is class action research method (PTK) which is implemented in two cycles which each cycle consists of four stages: planning, implementation, observation and reflection. Learning tools in this study are RPP, student interest questionnaire, test instrument sheet and student observation sheet. The results of the study were analyzed descriptively and obtained through the application of Reciprocal Teaching learning model with Game Smart Case can increase the students 'biology interest in class X3 SMA Negeri 1 Angkola Timur, especially the subject of ecosystem, based on the questionnaire of students obtained in cycle I of 65.80% And in cycle II equal to 81,13%. Based on student learning test in cycle I get completeness equal to 63,33% and cycle II equal to 83,33%, then based on student activity observation result obtained percentage equal to 62,90% and at second cycle equal to 80,83%. Based on the results of this study can be concluded that there is increased interest in learning biology of students through the learning model Reciprocal Teaching with Game Smart Case in class X3 SMA Negeri 1 Angkola Timur. Keywords:Interest in learning, Reciprocal Teaching model, Game Smart Case